ANALISIS KOMPETENSI DIGITAL GURU SEKOLAH MENENGAH KEJURUAN (SMK) DALAM MENUNJANG PROSES PEMBELAJARAN - Siti Laily Masnah, - (2023)
Digital competence is one of the challenges that teachers must possess to support the learning process based on the demands of the independent curriculum and the development of the times. However, issues related to information, utilization, and digital access limit the digital competence of teachers in supporting the learning process. The purpose of this study is to find out data on the level of digital competence of SMK teachers, data on digital training that has been attended by SMK teachers, the use of digital infrastructure by teachers, and the readiness of schools in facing digitalization.. The research method used is ex-post facto with a descriptive quantitative approach and survey technique. The study was conducted on SMK teachers majoring in Mechanical Engineering and Electrical Engineering at SMKN 8 Bandung. The research findings indicate that the digital competence of SMK teachers is quite good. Based on the distribution of questionnaires, the average digital competence is 69%. The digital competence of teachers is also influenced by several factors such as the digital training they have attended, with only 32% of SMK teachers having participated in digital training. The utilization of digital facilities in the school by some teachers is still not maximized, mainly due to difficulties in using the facilities and limited access experienced by teachers. The school's readiness to prepare for digitalization has reached 76.3%. These results indicate that the digital competence of SMK teachers and the school's readiness to face digitalization need to be improved.